Betalain production in plant in vitro systems - Georgie, V.; Ilieva, M.; Bley, T.; Pavlov, A.
Betalains have been widely used as natural colorants for many centuries, but their attractiveness for use as colorants of foods (or drugs and cosmetics)has increased recently due to their reportedly high anti-oxidative, free radical scavenging activities and concerns about the use of various synthetic alternatives. The main commercial sources of betalains are powders and concentrates of red beet (Beta vulgaris)or cactus pear (Opuntia ficusindica)extracts. However, in recent years the technical and commercial feasibility of various in vitro systems to produce them biotechnologically has been explored. These research activities have included assessments of novel approaches for cultivating plant cell or tissue cultures, and diverse bioreactor systems for increasing production levels of secondary metabolites. This paper reviews recent progress in plant in vitro systems for producing betalain pigments. In addition, the factors that could be manipulated, the bioreactor systems that could be used, and the strategies that could be applied to improve betalain production are discussed.
Keywords: BETALAINS; BIOLOGICAL ACTIVITY; BIOREACTORS; PLANT IN VITRO SYSTEMS; PROCESS OPTIMIZATION